Palladium and platinum in hydrothermal systems: The case of porphyry-Cu systems and sulfides associated with ophiolite complexes. - Eliopoulos, D.G.; Economou-Eliopoulos, M. (Bulletin of the Geological Society of Greece, 2013)
Data on the Pt and Pd contents in sea-floor massive sulfides related to ophiolite complexes indicated elevated Pt contents, up to 1 wt % Pt in sulfides from East Pacific Rise, up to 1000 ppb Pd or Pt in sulfides from mid-Atlantic Ridge and the Pindos ophiolite complex (Greece). Recently, elevated levels of Pd and Pt, have been reported from mineralization associated with alkaline porphyry deposits, such as the Skouries porphyry deposit (Greece), Cordillera of British Columbia, Elatsite (Bulgaria), Santo Tomas II in the Philippines and elsewhere. Current state of knowledge on the solubility of platinum-group elements was applied on hydrothermal systems related to the mineralization in ophiolite complexes and porphyry Cu-Mo-Au±Pd±Pt deposits toward a better understanding of the PGE mineralization in hydrothermal systems and the unknown Pd and Pt potential in porphyry-Cu systems. Ore reserves, mineralogical and geochemical ore data for porphyry-Cu systems are considered to be an encouraging factor for the presence of precious metals. In particular, the occurrence of merenskyite (palladium telluride) associated with chalcopyrite, coupled with the experimental data indicate that porphyry systems are capable to transport significant amounts of Pd and Pt.